Utilization of Balinese Folklore as Source of Value for the Social Studies: Perspective of Critical Education - Maryati, Tuty (Journal of Education and Vocational Research, 2015)
This paper is based on research study with the same title. Research is motivated by the existence of Bali as one of the islands in Indonesia, which is rich with various aspects of traditional culture, including a wide variety of folklore. Even Bali is also known as one of the saviors of Nusantara literary texts, especially from Java, Bali, and Lombok stored or written in the form of books or manuscripts (lontar). One of oral folklore is satua or Balinese folktale. It has many functions and strategic role, such as an endorsement tool for regulations and cultural institutions; as a compeller and supervisor to ensure the norms of society will always be adhered to collective members; and as a pedagogical device and learning for children, both in the family, the community as well as the school as a media, sources and learning agency. With qualitative approach, the text study toward three stories (satua), it was found the classical Balinese wisdom is very important for the students’ character development. Balinese folktales (satua) are also loaded with the Balinese dominant ideology such as Tri Hita Karana, the ideology of patriarchy and ideology of gender. Through perspective of critical education, these values can be utilized as source of social science learning in Junior High School.